Recent advances in assembled AIEgens for image-guided anticancer therapy. (7th October 2021) - Ren, Xue; Zhang, Song; Liu, Leijing; Xu, Bin; Tian, Wenjing
Abstract: Image-guided therapy, with simultaneous imaging and therapy functions, has the potential to greatly enhance the therapeutic efficacy of anticancer therapy, and reduce the incidence of side effects. Fluorescence imaging has the advantages of easy operation, abundant signal, high contrast, and fast response for real-time and non-invasive tracking. Luminogens with aggregation-induced emission characteristics (AIEgens) can emit strong luminescence in an aggregate state, which makes them ideal materials to construct applicative fluorophores for fluorescence imaging. The opportunity for image-guided cancer treatment has inspired researchers to explore the theranostic application of AIEgens combined with other therapy methods. In recent years, many AIEgens with efficient photosensitizing or photothermal abilities have been designed by precise molecular engineering, with superior performance in image-guided anticancer therapy. Owing to the hydrophobic property of most AIEgens, an assembly approach has been wildly utilized to construct biocompatible AIEgen-based nanostructures in aqueous systems, which can be used for image-guided anticancer therapy. In the present review, we summarize the recent advances in the assembled AIEgens for image-guided anticancer therapy. Five types of image-guided anticancer therapy using assembled AIEgens are included: chemotherapy, photodynamic therapy, photothermal therapy, gene therapy, and synergistic therapy. Moreover, a brief conclusion with the discussion of current challenges and future perspectives in this area is further presented.